Résolution adoptée par l' Assemblée Générale. La situation en Hongrie. A/RES/1312 (XIII), Treizième session, Point 69 de l'ordre du jour . Resolution Adopted by the General Assembly: the Situation in Hungary. A/RES/1312, Thirteenth Session, Agenda Item 69 - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. General Assembly This is 24-80-1-2 document in French.